2006
DOI: 10.1258/002367706777611415
|View full text |Cite
|
Sign up to set email alerts
|

Postanaesthetic tracheal strictures in three rabbits

Abstract: SummaryWithin an 11-day period, three rabbits were anaesthetized for neutering. All were endotracheally intubated with 12 cm long, 2.5 mm (inner diameter [ID]) polyvinylchloride (PVC) tubes. All rabbits developed clinical signs of dyspnoea and upper respiratory tract obstruction, 17-21 days later. One rabbit was found dead; the other two were treated, but one was euthanized and one died. At necropsy examination, focal chronic inflammation and significant localized narrowing of the tracheal lumen was found in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Similar findings have been reported in horses and our findings are consistent with those of Phaneuf et al, where histologic changes were reported after a single intubation event (the number of attempts was not reported) using both cuffed and uncuffed endotracheal tubes (7, 23). Since animals were euthanized at the end of our study, the consequences of the histologic changes are unknown; however, morbidity and mortality have been reported following apparently uneventful blind orotracheal intubations (7, 24). One rabbit in the SGAD group had a higher histological score, of 3.67, than the rest of the group.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been reported in horses and our findings are consistent with those of Phaneuf et al, where histologic changes were reported after a single intubation event (the number of attempts was not reported) using both cuffed and uncuffed endotracheal tubes (7, 23). Since animals were euthanized at the end of our study, the consequences of the histologic changes are unknown; however, morbidity and mortality have been reported following apparently uneventful blind orotracheal intubations (7, 24). One rabbit in the SGAD group had a higher histological score, of 3.67, than the rest of the group.…”
Section: Discussionmentioning
confidence: 99%
“…However this technique usually becomes a challenge in rabbits due to physiology and anatomy of the larynx and upper airways 6 . On the other hand sublaryngeal tracheal injuries, ulcerations and post anaesthetic tracheal strictures are reported in rabbits when using ET 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…Iatrogenic tracheitis has been found to be a cause of late postoperative death either as a result of chemical damage from inadequate rinsing after disinfection, or direct physical trauma from the endotracheal tube bevel (Grint and others 2006). Respiratory obstruction has been reported as a cause of death in rabbits (Brodbelt and others 2007); therefore, the maintenance of a patent airway is of great importance.…”
mentioning
confidence: 99%